Inflammatory effect of green propolis on dental pulp in rats - Mabel Rodrigues Alves Esmeraldo; Maria Goretti Freire de Carvalho; Rejane Andrade de Carvalho; Rennaly de Freitas Lima; Edja Maria Melo de Brito Costa (Sociedade Brasileira de Pesquisa Odontológica, 2013)
Pulpotomy in deciduous teeth is a controversial issue, especially with regard to alternative materials used for the direct pulp capping of the root canal pulp tissue. The aim of the present study was to perform a histological analysis of the initial reaction of the root canal pulp tissue in rats, following pulpotomy and pulp capping with (1) green propolis extract, (2) iodoform paste, (3) green propolis extract + iodoform and (4) calcium hydroxide paste with saline solution. Analyses were performed after 24 hours, 72 hours and 7 days. The substances containing green propolis extract and iodoform led to the production of an intense inflammatory infiltrate and necrosis in the root canal pulp tissue throughout the analyses. In the calcium hydroxide group, inflammatory infiltrate only prevailed at the 72-hour evaluation. Among the substances tested, calcium hydroxide paste induced the lowest intensity of inflammatory response in the root canal pulp tissue. Longer studies should be carried out to analyze the pulp repair process following pulpotomy and pulp capping with the compounds analyzed.